Pengaruh Mental Health bagi para remaja perspektif Al-Qur'an - Sabrina, Vina Nurin (Maliki Interdisciplinary Journal, 2024)
It is very important to understand the concept of mental health for teenagers, especially from an Islamic perspective. Considering that teenagers are very vulnerable to experiencing an identity crisis, the concept of mental health from an Islamic perspective can become the basis for teenagers' thoughts and actions. Adolescents are a society that experiences quite rapid growth and development both psychologically and physiologically, so that the condition of adolescents also influences thoughts and actions in everyday life. Therefore, there is a need for coaching and guidance for teenagers to be able to suppress the negative tendencies that exist in teenagers. And positive tendencies can be developed in a productive direction. In this case the presence of Islamic education is very important. Islamic education is a process of transformation and internalization of students' knowledge and values ​​through the growth and development of personal potential (fitrah) to achieve harmony and perfection in all aspects of life.